Features of generalized dynamics of quasiparticles in the presence of an external potential field. Part 2. Minkowski equations and degeneration of mobility in the strong fields - Suprun, A.D.; Shmeleva, L.V. (Functional Materials, 2016)
This article analyses the influence of the external electrostatic field (having an arbitrary space configuration) upon the properties of a free quasi-particle (for example, on the properties of the electron, which was injected into a semiconductor or into a dielectric). Approximations were formulated, that ensure fulfilment of the generalized Minkowski equations for the components of the external field for both methods of description: a quantum method of description within a local frame of reference and a classic method of description within a global frame of reference. It was demonstrated that the generalized dynamics of a quasiparticle in the external potential field might be one of the possible reasons of the abnormal mobility of carriers in the strong fields.